1990
DOI: 10.1073/pnas.87.19.7390
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr virus-encoded nuclear antigen 2 activates the viral latent membrane protein promoter by modulating the activity of a negative regulatory element.

Abstract: Previous studies suggest that the EpsteinBarr virus nuclear antigen EBNA2 participates in the regulation of the expression of the viral latent membrane protein (LMP). We have used reporter plasmids containing DNA fragments of the 5' flanking region of the LMP gene in cotransfection experiments to analyze the effect of EBNA2 on the activity of the LMP promoter. The results show that the LMP promoter is controlled by positive and negative transcription elements in a DNA fragment that contains the LMP transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
104
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(107 citation statements)
references
References 33 publications
3
104
0
Order By: Relevance
“…An alternative, and perhaps more likely, explanation of these data is that EBNA 6 in some way augments the action of, or cooperates with, EBNA 2 in increasing the expression of LMP. EBNA 2 activates the LMP gene by inducing transcription through an EBNA 2-responsive element located approximately 50 to 100 bp upstream of the transcriptional initiation site (Fahraeus et al, 1990;Wang et al, 1990b). EBNA 2 protein does not appear to bind directly to the DNA at this site and may act by counteracting the effects of a cellular repressor protein (Fahraeus et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An alternative, and perhaps more likely, explanation of these data is that EBNA 6 in some way augments the action of, or cooperates with, EBNA 2 in increasing the expression of LMP. EBNA 2 activates the LMP gene by inducing transcription through an EBNA 2-responsive element located approximately 50 to 100 bp upstream of the transcriptional initiation site (Fahraeus et al, 1990;Wang et al, 1990b). EBNA 2 protein does not appear to bind directly to the DNA at this site and may act by counteracting the effects of a cellular repressor protein (Fahraeus et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…EBNA 2 activates the LMP gene by inducing transcription through an EBNA 2-responsive element located approximately 50 to 100 bp upstream of the transcriptional initiation site (Fahraeus et al, 1990;Wang et al, 1990b). EBNA 2 protein does not appear to bind directly to the DNA at this site and may act by counteracting the effects of a cellular repressor protein (Fahraeus et al, 1990). At this stage we cannot exclude the possibility that EBNA 6 acts indirectly through some undefined cellular pathway or even acts post-transcriptionally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that EBNA2 and EBNA leader protein (EBNA-LP) cooperate to induce the transition of the infected cells from G0 to G1 (Sinclair et al, 1994). EBNA2 also activates the transcription of all viral proteins expressed in lymphoblastoid cell lines by transactivating: (i) the BamH1-C-promoter (Cp) (Sung et al, 1991), from which transcription of all EBNA genes is controlled; (ii) the promoters of LMP1 and LMP2 (Abbot et al, 1990;Fahraeus et al, 1990). Oncogenic potential of LMP1, frequently expressed in several EBV-associated cancers, is consistent with its ability to transform fibroblasts and to inhibit epithelial differentiation (Dawson et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…We and others have demonstrated that the regulatory region of the LMP1 EBV gene contains cis-acting elements that mediate the EBNA2-induced up-regulation of LMP1 expression (FAhraeus et al, 1990;Ghosh & Kieff, 1990). To define further the LRS elements involved in interactions with transcription factors in B cells differing in EBNA2 expression, DNase footprinting experiments were performed.…”
Section: Dnase I Protection Analysismentioning
confidence: 98%